Evolution of Pelage Luminance in Squirrels (Sciuridae) - Sheets, Alec D.; Chavez, Andreas S. (Frontiers in Ecology and Evolution, 2020)
Pelage luminance has been found in many mammalian systems to follow patterns predicted by Gloger’s rule where darker colored animals are associated with environments that are warmer and more moist. Sciurids have one of the greatest diversities of color patterns and hues among mammalian families. We have used comparative methods to investigate whether the luminance of dorsal pelage in 137 species across Sciuridae conform to prediction of Gloger’s rule and other background matching expectations. We found using phylogenetic multiple regression, as well as univariate regression, that Sciurids generally conform to expectations of Gloger’s rule. Darker species are associated with environments with higher primary productivity, higher temperature, higher humidity, and lower solar radiation. Moreover, in support of the predictions of background matching, darker squirrel species were associated with environments with greater soil carbon content and higher fire frequency. Our macroevolutionary study sheds some light on selective pressures that are driving the evolution of coloration in Sciurids, but more comparative research is needed to fully understand other selective pressures that have led to the wide diversity of color patterns and hues.